Time for Adopting International Financial Reporting Standards (IFRS) - Saini, AL.; Mittal , A. K. (Gyan Management Journal, 2011)
Financial boundaries among countries have been disappearing and their financial markets are behaving in tandem with each other. It could be seen in stock markets, commodity markets, and also the financial downside/upside of a country affecting the economies of other countries. These are some of the reasons for adopting a uniform high quality financial reporting standards world over. The existence of a global benchmark enables direct comparison of corporate financial reports anywhere, anytime and by anyone. Such high quality standards enhance investor's confidence by allowing economic transactions of a similar nature to be treated and reflected in the same manner around the globe. Globalization in itself intends to institutionalize a rule-based world economy, trade and investment without barriers. The very architecture and drive of globalization is global finance, which is driven by Investment Bankers, rating agencies and financial professionals.
Keywords: (IFRS); financial markets; commodity markets; economic transactions; globalization